A short review on different metal alloys on rapid cooling process - M., Ishak; Norazlianie, Sazali; M. F., Ghazali (IOP Publishing, 2020)
This review is being undertaken to compare the effect of rapid cooling process of variation metal alloys and make observation about microstructure and hardness. Types of metal alloys involve in this experiment are mild steel, stainless steel and brass. All of the specimens prepared with same shape and size which is 4mm. Nowadays there are many manufacturing industries that provide their own standard operation procedure (SOP) to create a better quality in producing product, one of the aspect that always be considered is about the strength. To understand the process, concept and mechanical properties about the material used are too important to produce or design the best product. All material have their own identities so we try to use different metal alloys and compare which one will give the best results according to our objective to evaluate based on microstructure and hardness in two different method which are slow cooling and fast cooling. All specimens are setup with our own parameter and heat up until reach certain temperature, and after specimens take it out from furnace we will separately do cooling process in two different method which are quenching and normalizing. As we knows every metal will change their properties by heat, heat treatment and rapid cooling will be the higher contribution to ensure the hardness and microstructure. This research show the results between three specimens, mild steel have the best option to be selected because tally with our objective and it have a better strength also supported by their microstructure results.